Altered Expression of CD300a Inhibitory Receptor on CD4+ T Cells From Human Immunodeficiency Virus-1-Infected Patients: Association With Disease Progression Markers - Vitallé, Joana; Terrén, Iñigo; Gamboa-Urquijo, Leire; Orrantia, Ane; Tarancón-Díez, Laura; Genebat, Miguel; Ruiz-Mateos, Ezequiel; Leal, Manuel; García-Obregón, Susana; Zenarruzabeitia, Olatz; Borrego, Francisco (Frontiers in Immunology, 2018)
The ability of the CD300a inhibitory receptor to modulate immune cell functions and its involvement in the pathogenesis of many diseases has aroused a great interest in this molecule. Within human CD4+ T lymphocytes from healthy donors, the inhibitory receptor CD300a is differentially expressed among different T helper subsets. However, there are no data about the expression and regulation of CD300a receptor on CD4+ T cells from HIV-1 infected patients. The objective of this study was to investigate the expression of CD300a on CD4+ T cells from HIV-infected patients on suppressive combined antiretroviral treatment (cART) and cART naïve patients. Our results have demonstrated that the expression levels of this inhibitory receptor were higher on CD4+ T cells from HIV-1 infected subjects compared with healthy donors, and that cART did not reverse the altered expression of CD300a receptor in these patients. We have observed an increase of CD300a expression on both PD1+CD4+ and CD38+CD4+ T cells from HIV-1 infected people. Interestingly, a triple positive (CD300a+PD1+CD38+) subset was expanded in naïve HIV-1 infected patients, while it was very rare in healthy donors and patients on cART. Finally, we found a negative correlation of CD300a expression on CD4+ T lymphocytes and some markers associated with HIV-1 disease progression. Thus, our results show that HIV-1 infection has an impact in the regulation of CD300a inhibitory receptor expression levels, and further studies will shed light into the role of this cell surface receptor in the pathogenesis of HIV infection.